The Functionality of CD8 + T Lymphocytes during Active Lung Tuberculosis in HIV Infection - Miguel Alfonzo; José Suárez; Mario Gomegna; Patricia Valenzuela; Alida Hung; Dimas Hernández (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2012)
The role of CD4+ T-cells in immunity against tuberculosis has been extensively studied.However, the function of CD8+ T-cells in co-infections of HIV-1 and M. tuberculosis (VIH/Mtb) is not well understood. To evaluate the functionality of CD8+ T-cells from HIV+ patients having active TB, several immunological parameters were assayed. Results indicate that both HIV+ groups (with and without active TB), having the same viral load and peripheral blood CD4+ T and amount of lymphocytes in the blood, displayed different alterations in the ex vivo frequency for CD95 and CD127 markers in CD8+ T-cells, naive and memory positive cells, while for the HLA-DR marker, differences were observed in the total cell population. Moreover, CD8+ T- cells from TB-active patients, cultured for 72 h in the presence of PPD, showed a low proliferation rate and a high frequency of induced apoptosis as well as lower production of IFN-y IL-10 and TNF-a cytokines compared to healthy control cells. These results support the hypothesis that CD8+ T-cells lose their functionality against Mtb during an HIV-1 infection, which could be responsible for the activation of TB in VIH/Mtb co-infected patients.